(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This study explores the borrowing of sports terminology into the Karakalpak language, focusing on linguistic, cultural, and social dimensions. It highlights the influence of Russian during the Soviet period and the growing role of English due to globalization and digital media. The paper examines phonological and morphological adaptations of borrowed terms, their integration into Karakalpak society, and ongoing debates about language purity. Comparative analysis with other Turkic languages reveals shared patterns and regional variations. Ultimately, the dynamic incorporation of sports terms illustrates the adaptability of Karakalpak in the face of global cultural flows while retaining its linguistic identity.